2004
DOI: 10.1111/j.1471-6712.2004.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and characteristics of help provision for elderly people living at home and in relation to quality of life

Abstract: The aim of this study was to investigate determinants of help from informal or formal caregivers or a combination of both among people aged 75 or more and living at home, and the characteristics of the recipients, the help they received and their quality of life (QoL). The sample for this study was 448 elderly people, 75-99 years of age, living at home and receiving help with activities for daily living, instrumental or both instrumental and personal. Regression analysis showed high QoL not to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 19 publications
7
36
2
4
Order By: Relevance
“…With regard to disabilities, there was a direct connection between disabilities and QOL. The finding is consistent with some previous studies [27,29]. The result of this study is also in line with that of Bindawas, et al, [30] indicated that increased levels of lower extremity performance was associated with slower rates of decline in physical and mental health-related QOL among older Mexican Americans.…”
Section: Discussionsupporting
confidence: 83%
“…With regard to disabilities, there was a direct connection between disabilities and QOL. The finding is consistent with some previous studies [27,29]. The result of this study is also in line with that of Bindawas, et al, [30] indicated that increased levels of lower extremity performance was associated with slower rates of decline in physical and mental health-related QOL among older Mexican Americans.…”
Section: Discussionsupporting
confidence: 83%
“…The age-related deterioration in PCS seems to be an innate characteristic, but the MCS score is susceptible to environmental factors. It seems that if older people have satisfactory living conditions, psychological health does not deteriorate substantially [40]; environmental and cultural factors are more important determinants of MCS than physical status.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, a sample of persons aged 75 years and over who lived at home but only received help with ADL has been studied. Among them, 45% did receive informal care, 15% formal care and 40% mixed care [42].…”
Section: Informal Formal or Mixed Carementioning
confidence: 99%